A Case of Streptococcus intermedius Abscess Within a Malignant Neck Mass and Review of the Literature. Issue 5 (15th September 2021) - Cummins, Kaelyn C.; Lin, Doris
Abstract: Streptococcus intermedius is an organism found commensally in various mucosal sites. Over the past couple decades, it has been recognized as a cause of severe pyogenic infections in sites including the brain, liver, lung, head and neck. Here, we describe an uncommon case of S. intermedius infection in a patient with tonsillar squamous cell carcinoma and a metastatic neck mass with overlying postradiation skin changes. We also review the literature on this pathogen in cancer patients because it remains understudied despite its pathogenicity.